“Trust but not blind trust”: accounting controls and level-specific budget decoupling in a public-sector organization - Anatoli Bourmistrov; Katarina Kaarbøe; Thea Sandness; Elise Skaue (Journal of Public Budgeting, Accounting & Financial Management, 2026)
Purpose This paper aims to examine how a beyond budgeting (BB)-inspired reconfiguration of accounting controls supports trust-based management practices in a public-sector organization operating under annual budget constraints. While BB advocates replacing traditional annual budgeting with more adaptive and trust-based approaches, public organizations face strong accountability demands that make the abandonment of annual budgets difficult. Design/methodology/approach This study is based on a longitudinal, exploratory case study of the National Service and Call Center at Norway’s Labour and Welfare Administration. Data were collected through in-depth interviews with managers and employees, as well as an analysis of internal documents, reports and governmental directives. Findings The study shows how annual budgeting was decoupled across organizational levels. While annual budgets were retained for political and departmental accountability, budget-based resource pre-allocation was abandoned at the operational level. Instead, the organization developed oversight controls – periodic, transparent and comparative accounting practices such as cost monitoring, forecasting and internal benchmarking. These controls supported decentralized decision-making, while preserving financial discipline based on values-based decision-making. The findings further show that increased autonomy fostered trust but also generated employee anxiety, which was mitigated through intensified leadership practices supported by oversight control mechanisms. Originality/value The study contributes to the trust–control literature by demonstrating how accounting controls can complement trust-based management, and to BB research by showing how BB principles can be adapted to public-sector contexts.